The mediating roles of communication in expatriate adjustment - Halim, Haslina; Abu Bakar, Hassan; Mustaffa, Che Su (Universiti Teknikal Malaysia Melaka, 2016)
This study examines the mediating effects of communication and interaction on the relationships between individual, organizational and non-work variables and expatriate adjustment.We tested the model by using structural equation modeling with data obtained from 203 hotel expatriates in Malaysia. The analyses found that the link between previous international experience (individual), social support (organizational) and family adjustment (non-work) and expatriate adjustment was partially mediated by perceived communicative and interaction adaptability. These findings validated the proposed model and, in particular, the central role of communication in cross-cultural adjustment processes in workplace is empirically confirmed. Practical implications are also discussed in the paper.